Community Entrepreneurship Development in Mae Sa - Kog Ma UNESCO Biosphere Reserve, Chiang Mai Province - Suwanna, Anavin; Chaiprakong, Thodsaporn; Nimitkul, Chortip; Keatipong, Kamol; Aramsri, Kritsana (Area Based Development Research Journal, 2021)
Mae Sa - Kog Ma biosphere reserve in Chiang Mai province has recently attracted tourism entrepreneurs and the area has served extended tourism operational activities. Meanwhile, the activity designs of entrepreneurs are seen to lack linkage to biosphere reserve value and local people’s way of life. This paper aims to explore and design the technical tour activities based on community participation and to develop community entrepreneurs in the Mae Sa - Kog Ma biosphere reserve. Participatory Action Research (PAR) as an operational tool is used for the following operations: 1) development of technical tour activities; 2) community entrepreneurship development; and 3) Mae Sa – Kog Ma biosphere reserve conservation and development with the integrated concepts of sustainable development, community entrepreneurship, appreciate influence control (AIC), and technical tour activities development. The operation results are seen in three aspects, which are, 1) six community entrepreneurship prototypes, 2) ten operational strategies of technical tour activities, and 3) nineteen technical tour activities. Additionally, the economic benefits in three months were an increase in the entrepreneur’s revenue of 103,430 baht, a generated income from local employment of 12,000 baht, and a generate turnover income to the community from trading seasonal native plants of 8,090 baht. As the community entrepreneurs go through the learning process, they can organize technical tour activities. Next, they can transfer knowledge and share the experiences with other entrepreneurs to develop business alliances and collaborative networks with related organizations. Ultimately, the study can contribute to driving the Mae Sa - Kog Ma biosphere reserve as a sustainable technical tour destination.